2018
DOI: 10.24843/jim.2018.v06.i03.p04
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Augmented Reality Video Dinamis dalam Pembelajaran Peredaran Darah Berbasis Android

Abstract: Peredaran darah merupakan suatu pelajaran penting yang harus diketahui oleh siswa siswi dalam pelajaran biologi. Banyak siswa yang kurang dalam pemahaman saat dijelaskan dengan buku atau alat peraga. Terbatasnya alat peraga dan ketertarikan para siswa untuk belajar mendominasi pemanfaatan alat elektronik sebagai bahan ajar. Teknologi yang semakin canggih dapat dimanfaatkan sebagai sarana belajar mengajar yang menarik. Penerapan teknologi augmented reality dalam pembelajaran peredaran darah menjadi salah satu s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In line with the expression (Mukti & Nurcahyo, 2017) that the use of learning media can increase learning motivation during teaching and learning activities. In addition, the results of this research align with the results of research (Astiti et al, 2018), which concluded that learning through mobile can increase learning motivation in circulatory system material.…”
Section: Analysis Of the Effect Of Learning Using Educational Games O...supporting
confidence: 80%
“…In line with the expression (Mukti & Nurcahyo, 2017) that the use of learning media can increase learning motivation during teaching and learning activities. In addition, the results of this research align with the results of research (Astiti et al, 2018), which concluded that learning through mobile can increase learning motivation in circulatory system material.…”
Section: Analysis Of the Effect Of Learning Using Educational Games O...supporting
confidence: 80%
“…The same research was also conducted by Fitriani who discussed the development of AR-based learning media regarding the introduction of organs in the human body [12]. Astiti's research, explores the application of dynamic video AR in android-based circulatory learning, with the hope that it can help teachers in delivering material, especially regarding blood circulation, and attract students to learn and understand the material [13].…”
Section: Introductionmentioning
confidence: 97%
“…5) children have difficulty in improving fine motor skills in recognizing animal material, 6) Kindergarten teachers Harapan Bunda Semarang are 100% interested in using VAR-based educational games to support the process of learning [3]. This is due the experiences or memories of that period will greatly influence the person in later years next, while according to Piaget the age is zero to six years includes two periods of cognitive development, namely the sensorimotor phase (0-2 years) where Children's knowledge is obtained through physical interaction, either with people or objects and preoperational phase (2-6 years) where children begin to use symbols for represent the world of the environment cognitively, so media is needed learning that is able to display these symbols according to the level of thinking of kindergarten children [4], then using augmented reality-based media increases kindergarten students' learning motivation [5].…”
Section: Introductionmentioning
confidence: 99%